LncRNA SNHG5 promotes cervical cancer progression by regulating the miR-132/SOX4 pathway - Liqin Zhang; Xiaoming Wu; Yue Li; Xianlin Teng; Libo Zou; Beiwei Yu (Autoimmunity, 2021)
Background The long non-coding RNA (lncRNA) small nucleolar RNA host gene 5 (SNHG5) has been verified as a crucial regulator in many types of tumours but not clear in cervical cancer (CC). This study aims to investigate the effect and further mechanisms of lncRNA SNHG5 in CC. Methods The expression of SNHG5 and miR-132, as well as SOX4 (sex-determining region Y-box 4) mRNA expression were determined by quantitative real-time PCR (qRT-PCR). The protein level of SOX4 and epithelial-mesenchymal transition (EMT)-related proteins were evaluated by western blot. Then, Edu and Transwell assay were performed to assess the proliferation, migration and invasion of CC cells. RNA immunoprecipitation (RIP) and RNA pull-down assay were conducted to explore the relationship between SNHG5 and miR-132. Results SNHG5 and SOX4 were upregulated, and miR-132 was downregulated in CC tissues and cell lines. SNHG5 was positively correlated with FIGO stage (p = .003) and lymph node metastasis (p = .001). Pearson’s correlation analysis conveyed that SNHG5 was positively correlated with SOX4, and miR-132 was negatively correlated with SOX4 and SNHG5. Knockdown of SNHG5 in vitro reduced CC cell proliferation, migration and invasion through regulating miR-132. Moreover, overexpression of miR-132 restrained CC cell proliferation, migration, and invasion through targeting SOX4, and SNHG5 enhanced SOX4 expression via negatively regulating miR-132. Conclusion SNHG5 promotes SOX4 expression to accelerate CC cell proliferation, migration and invasion through negatively regulating miR-132.